Seismic exploration survey northeast of the Tres Virgenes Geothermal Field, Baja California Sur, Mexico: A new Geothermal prospect - Sena Lozoya, Eleyra Berenice (2019)
Geophysical prospecting has become essential to identify low enthalpy areas with geothermal potential, mainly, for direct uses. The present study uses two seismic techniques and lithological information from shallow boreholes located northeast of the Tres Virgenes Geothermal Field, B.C.S., Mexico, to identify geological structures of geothermal interesting. Using the Multichannel Analysis of Surface Waves method (MASW), it was possible to correlate the S-wave velocity model with the lithology from two wells drilled over the seismic profile. Additionally, we generated a seismic reflection model to describe the geological distribution of deeper structures. The reflection profile, which reached depths of about 500 m, was complemented with superficial information from a MASW velocity model. We found a relationship between the velocity distribution of P and S waves from both models. The integration of seismic and lithological information allows us to identify a very fractured subsurface and a deep zone with possible geothermal interest.